2016
DOI: 10.1111/bph.13431
|View full text |Cite
|
Sign up to set email alerts
|

Effects of new‐generation inhibitors of the calcium‐activated chloride channel anoctamin 1 on slow waves in the gastrointestinal tract

Abstract: BACKGROUND AND PURPOSEHigh-throughput screening of compound libraries using genetically encoded fluorescent biosensors has identified several secondgeneration. low MW inhibitors of the calcium-activated chloride channel anoctamin 1 (CaCC/Ano1). Here we have (i) examined the effects of these Ano1 inhibitors on gastric and intestinal pacemaker activity; (ii) compared the effects of these inhibitors with those of the more classical CaCC inhibitor, 5-nitro-2-(3-phenylpropylalanine) benzoate (NPPB); (ii) examined t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(52 citation statements)
references
References 43 publications
3
48
0
1
Order By: Relevance
“…Our findings strongly suggest that the generation and propagation of slow waves in the ICC in the proximal intestine of shorthorn sculpin is fundamental for the initiation and propagation of in vivo gastrointestinal motility patterns. Similar results have been observed in a range of mammals, as pharmacological blockade of Ano1 expressed in ICC prevented the generation of slow waves in the stomach and intestine with consequent adverse effects on gastrointestinal motility (Hwang et al, 2016(Hwang et al, , 2009Zhu et al, 2009). Our findings concerning the function of ICC in the gastrointestinal tract of fish are also in line with observations made on the embryonic intestine of zebrafish, which show that the appearance of Ano1-positive cells (Uyttebroek et al, 2013) coincides with the onset of propagating contractions (Holmberg et al, 2003).…”
Section: Role Of Icc In the Control Of Gastrointestinal Motility In Fishsupporting
confidence: 90%
“…Our findings strongly suggest that the generation and propagation of slow waves in the ICC in the proximal intestine of shorthorn sculpin is fundamental for the initiation and propagation of in vivo gastrointestinal motility patterns. Similar results have been observed in a range of mammals, as pharmacological blockade of Ano1 expressed in ICC prevented the generation of slow waves in the stomach and intestine with consequent adverse effects on gastrointestinal motility (Hwang et al, 2016(Hwang et al, , 2009Zhu et al, 2009). Our findings concerning the function of ICC in the gastrointestinal tract of fish are also in line with observations made on the embryonic intestine of zebrafish, which show that the appearance of Ano1-positive cells (Uyttebroek et al, 2013) coincides with the onset of propagating contractions (Holmberg et al, 2003).…”
Section: Role Of Icc In the Control Of Gastrointestinal Motility In Fishsupporting
confidence: 90%
“…CaCCinh-A01 and T16Ainh-A01 are the most potent inhibitors of calcium-activated Cl − conductance and are typically used to examine the contributions of CaCCs/ANO1 in physiological models, although their specificity remains uncertain [8,16]. CaCCinh-A01 can completely block CaCC current in human bronchial and intestinal epithelial cells, whereas T16Ainh-A01 poorly inhibits total CaCC current, but blocks an initial agonist-stimulated transient chloride current [34]. CaCCs are activated by an increases in the level of intracellular free calcium, and Cl − flux through CaCCs is generally thought to be driven by ANO1 or ANO2 [8].…”
Section: Cellular Physiology and Biochemistrymentioning
confidence: 99%
“…Taken together, pacemaker potentials in small intestinal ICC were unchanged by the knockdown of ANO1, whereas the frequency of pacemaker potentials in colonic ICC was reduced by knockdown of ANO1. Thus, our results provide evidence that ANO1 might not contribute to the generation of pacemaker potentials in small [25] reported that in intact small intestinal tissues of the mouse, slow waves were inhibited by high concentrations of CaCCinh-A01 (30 µM); however, slow waves were still generated in the presence of high concentrations of T16Ainh-A01. They explained that the difference in drug sensitivity might be due to the possibility of different splice variants.…”
Section: Discussionmentioning
confidence: 53%
“…Thus, their effect on ANO1 pacemaker channels in ICC is still unclear. Recently, new selective ANO1 inhibitors (CaCCinh-A01, T16Ainh-A01, and MONNA) have been discovered and used for studying Ca 2+ -activated Cl -channels [22][23][24][25]. In the present study, it was shown that CaCCinh-A01, T16Ainh-A01, and MONNA had different effects on pacemaker activity in small intestinal and colonic ICC.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation